Content Analysis of Da’wa Message in “Laa Tahzan: Don’t Be Sad” Episode #71 - #80 On Line Webtoon - Prihananto, Prihananto; Rachman, M. Faizal; Nisak, Fika Khoirotun (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
The focus of the problems studied in this thesis is: How is the message of da’wa contained in the Webtoon